RENDEMEN DAN pH GELATIN KULIT IKAN NILA (Oreochromis niloticus) YANG DIRENDAM PADA BERBAGAI KOSENTRASI HCl - Renol Renol; Finarti Finarti; Deddy Wahyudi; Mohamad Akbar; Radhiyatul Ula (Jurnal Pengolahan Pangan, 2018)
Gelatin is derivative protein of collagen fiber which is found in the skin, bone, and cartilage. The composition of amino acids is almost similar to collagen, where glycine as the main amino acid and as 2/3 of all the amino acids that make it up, where 1/3 of the amino acids contained by proline and proline hydroxine. This research aims at knowing the physical charateristic of rendement and pH by using the skin of tilapia (Oreochromis niloticus) in concentration of HCL as immersion solution. The benefits of this research are expected to be the information sources of gelatin making in production scale, especially the gelatin production from the skin of tilapia (Oreochromis niloticus). The information are expected to support the development of information science and technology (IPTEK). Gelatin of tilapia skin (Oreochromis niloticus) used Completely Randomized Design (RAL) with 4 treatments. The treatments were HCl immersion to Tilapia’s skin (Oreochromis nilaticus) with N1 (4%), N2 (5%), N3 (6%) and N4 (7%) in 4 times repetitions